Global research of artificial intelligence in strabismus: a bibliometric analysis - Zhou, Ziying; Zhang, Xuan; Tang, Xiajing; Grzybowski, Andrzej; Ye, Juan; Lou, Lixia (Frontiers in Medicine, 2023)
Purpose: To analyze the global publications on artificial intelligence (AI) in strabismus using a bibliometric approach. Methods: The Web of Science Core Collection (WoSCC) database was used to retrieve all of the publications on AI in strabismus from 2002 to 2023. We analyzed the publication and citation trend and identified highly-cited articles, prolific countries, institutions, authors and journals, relevant research domains and keywords. VOSviewer (software) and Bibliometrix (package) were used for data analysis and visualization. Results: By analyzing a total of 146 relevant publications, this study found an overall increasing trend in the number of annual publications and citations in the last decade. USA was the most productive country with the closest international cooperation. The top 3 research domains were Ophthalmology, Engineering Biomedical and Optics. Journal of AAPOS was the most productive journal in this field. The keywords analysis showed that “deep learning” and “machine learning” may be the hotspots in the future. Conclusions: In recent years, research on the application of AI in strabismus has made remarkable progress. The future trends will be toward optimized technology and algorithms. Our findings help researchers better understand the development of this field and provide valuable clues for future research directions.